Analisis Buku Bahasa Arab Tujuan Khusus: Bahasa Arab untuk Ekonomi dengan Standar 5C oleh The National Standards in Foreign Language Education Project - Fitra, Muh. Naufal; Wazkia, Hanif; Rosyidi, Abdul Wahab; Tamam, Muhammad Ibnu; Ilahi, Muhamad Muzaki Kurnia (Universitas Lampung, 2024)
Arabic has an important role in global communication, including in the economic field. This is due to the rapid economic development of the Middle East which emphasizes the importance of mastering the Arabic language. One of the books that is a resource for learning Arabic for economic purposes is